Peran Pemimpin Pondok Pesantren dalam Membentuk Kepribadian Santri Ideal menurut Kitab Taʻlīm al-Mutaʻallim - Meila Sari; Adi Riyanto; Cecep Safrudin; Elisa Rumzanah; Endang Sukaesih; Haikal Haikal; Irhamuddin Irhamuddin (KURAS Institute, 2022)
The role of Islamic boarding school leaders is crucial in shaping the character of students (santri), as they function not only as institutional heads but also as second parents to the students. These leaders hold the responsibility of nurturing student personalities in alignment with Islamic values. This study aims to explore the significance of leadership roles in character development and to examine the specific efforts taken by leaders based on the Ta'lim al-Muta'allim framework. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, field observations, and documentation. The findings reveal that the leadership of Islamic boarding schools plays a vital role in the formation of student character. The personal traits and moral conduct of the leaders serve as role models, while their advice provides ethical guidance. Character development efforts include regular study sessions of the Taʻlīm al-Mutaʻallim book after evening prayers, supported by methods such as exemplary behavior, moral instruction, and interactive discussions.